Seasonal variability of the main components in essential oil of Mentha × piperita L. (23rd July 2014) - Grulova, Daniela; De Martino, Laura; Mancini, Emilia; Salamon, Ivan; De Feo, Vincenzo
Abstract BACKGROUND Mentha × piperita is an important and commonly used flavoring plant worldwide. Its constituents, primarily menthol and menthone, change in the essential oil depending on internal and external factors, of which environmental conditions appear very important. The experiment was established in 2010 for three vegetation season, in order to observe the quantitative changes of the main components of peppermint. The determination of menthol, menthone, limonene, menthyl acetate, menthofuran and β‐caryophyllene was registered. RESULTS In the experimental season 2011 and 2012 a higher mean temperature than in 2010 and extreme rainfall in July 2011 and 2012 were recorded. Different environmental conditions affected the development of M. × piperita plants and the content and composition of the essential oil. CONCLUSION Seasonal and maturity variations are interlinked with each other, because the specific ontogenic growth stage differed as the season progressed. Fluctuations in monthly and seasonal temperature and precipitation patterns affected the quality of peppermint essential oil. © 2014 Society of Chemical Industry